CONTENT OF FORMING COMMUNICATIVE COMPETENCE IN PRIMARY SCHOOL STUDENTS THROUGH GAMIFICATION - Zarimbetova, Gulzira Kosherbayevna; Aminova, Xushnoza Baxodirovna; Nuriddinova, Rukhshona Dastanbekovna (SCIENCE and SOCIETY, 2026)
The article examines the significance and substantive foundations of gamification technology in the process of developing communicative competence among primary school students. The influence of gamification on the components of communicative competence, its didactic potential, and its role within the context of primary education are discussed. The article analyses the structural composition of communicative competence, the pedagogical functions of gamification elements, and their interrelationship. The findings indicate that a gamification-based approach can make a substantial contribution to the development of speech activity, communication culture, and a disposition toward collaborative engagement among primary school students.